Implementation of the Laravel Framework in the Development of Sales and Repair Information Systems at Vespa Clinic Kotabumi - Gaib Wiwaha, Gigant; Sulistiani, Heni (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
The existence of realtime, fast and accurate information is very important for human survival. Website-based information systems provide accessibility for consumers to access information without time limitations and interactivity provided by producers to consumers by offering various interactive features as a form of online consultation. The purpose of this research is to implement a website for sales and repairs using the Laravel Framework at Vespa Clinic Kotabumi (Vecko) and to facilitate management and bookkeeping that is fully recorded on the Web. The method used is Waterfall development with the application of blackbox testing methods and Mean Opinion Score. Researchers made the Vespa Clinic Kotabumi Workshop as the object of research. Data collection techniques in this study are interviews and observations. In this case, the creation of information systems is expected to increase income with faster and more efficient business processes and expand the reach of information. The results of the research are a form of implementation of the Laravel Framework in the sales and repair system at the Kotabumi vespa workshop equipped with attractive features for admin and customers consisting of reservation, product page, and confirmation. In this research, the Laravel Framework has succeeded in maximizing the development of the sales website. The sales system becomes more efficient and greatly helps transactions between sellers and buyers. The use of Laravel framework on this system has helped and facilitated the development of the system in this study